International Judo Coaches Alliance
Internetseite der, z. Z. mit folgenden Artikeln zum Training in der Sportart Judo: The Training Session - by Amos Gil'ad, 6th Dan Evaluation of the Technical and Tactical Aspects of Judo Matches at the Seniors Level - by Stanislaw Sterkowicz and Pawel Maslej Nomenclature - by Amos Gil'ad, 6th Dan Overtraining - by Amos Gil'ad, 6th Dan 98 Jr World Championships - Cali, Colombia Judo Vision 2000 - an IJF blueprint for the future of Judo Periodisation in Judo Training - by Amos Gil'ad, 6th Dan